PERUBAHAN STRUKTUR ORGANISASI DAN DAMPAKNYA TERHADAP LAYANAN DAN SDM: STUDI KASUS PUSAT DATA DAN LAYANAN INFORMASI PERUM LKBN ANTARA - Nurul Safira Anindita; Fuad Gani (Faculty of Economics and Business | Universitas Diponegoro, 2019)
This final project discusses changes in organizational structure at the Pusat Data dan Layanan Informasi Perum LKBN Antara and looks at the impact on their services and human resources. This research uses qualitative research with a case study method and data collection using interview techniques and document studies. The results of this study show that the changes that occurred at the PUSDATIN Antara were the increasing in work units that previously only handled text data and library services, now handling photo and video data services as well. However, the changes that occur at the PUSDATIN Antara are still in the changing phase, not until the final phase yet, which is the freezing phase. This current phase has made some impacts on human resources and services provided by the PUSDATIN Antara. The impact on human resources is the lack of employees to handle photo data services, while the impact on services is the lack of integration of video data services.